Periodontal Disease and Obstructive Sleep Apnea: Shared Mechanisms, Clinical Implications, and Future Research Directions - Serena Incerti Parenti; Claudio Cesari; Veronica Della Godenza; Matteo Zanarini; Francesca Zangari; Giulio Alessandri Bonetti (Applied Sciences)
This review explores the emerging relationship between obstructive sleep apnea (OSA) and periodontal disease (PD), emphasizing shared inflammatory pathways, overlapping risk factors, and potential systemic health implications. Both conditions are characterized by chronic inflammation and oxidative stress, which independently contribute to cardiovascular disease, diabetes, and other systemic disorders. Evidence suggests a bidirectional relationship, with OSA-related hypoxia exacerbating periodontal tissue breakdown and PD-induced inflammation potentially influencing OSA severity. However, the causative nature of the relationship between OSA and PD remains uncertain, largely due to inconsistencies in diagnostic criteria, methodological variability, and study heterogeneity. This review highlights the essential role of systematic reviews (SRs) in synthesizing current evidence, identifying research gaps, and guiding future studies. To maximize their impact, SRs should adhere to rigorous methodological quality standards, improve transparency in data reporting, and address the heterogeneity of included studies. Future research should focus on longitudinal and interventional designs, standardize diagnostic protocols, and investigate biomarkers, oral microbiome profiles, and inflammatory mediators to elucidate the mechanisms linking OSA and PD. Multidisciplinary collaboration between dental and sleep specialists is crucial to advancing evidence-based strategies that improve patient outcomes and address the broader health implications of these often coexisting conditions.